THE METHODOLOGICAL FOUNDATION OF CONTEMPORARY ENGINEERING EDUCATION IS THE FUSION OF EDUCATION, SCIENCE AND INDUSTRY - Samadova Malika Xasan qizi (Western European Studies, 2024)
Presently, there is a significant societal emphasis on nurturing well-rounded, spiritually mature, economically savvy, critical-thinking, highly educated, and cultured young individuals. This article discusses the importance of fostering students' professional competence within the educational framework, along with methods for cultivating concepts of professional competence, personal achievement, and competitiveness.
Keywords: competency; experiential foundation; educational and methodological resources